PEMBELAAN TERPAKSA PADA TINDAK PIDANA PEMBUNUHAN(PUTUSAN NOMOR 14/Pid.B/2021/PN Wgw): Defense of Necessity in the Crime of Murder (Decision Number 14/Pis.B/2021/PN Wgw - Aryaputra, Ivan Andhika; Wangga, Maria Silvya E. (AMICUS CURIAE, 2024)
Involuntary defense (noodweer) justifies an action if it is involuntary, undertaken to defend oneself or others from an imminent threat that violates the law. Individuals who use duress defense have the right to be free from prosecution. The case study occurred in Liya Togo Village, South Wangi-Wangi, Wakatobi Regency, starting from an argument between the victim and the perpetrator. The victim thrust a badik, threatening the perpetrator's life, which was parried. The perpetrator, faced with an urgent attack from the victim, resorted to forced defense by drawing his badik, causing the death of the victim. The research problem involves the judge's consideration of the elements of Article 338 of the Criminal Code and whether the perpetrator's actions meet the elements of Forced Defense in accordance with Article 49 of the Criminal Code. The research method uses a normative legal approach with secondary data from primary, secondary, and tertiary legal materials. The research concluded that the judge's consideration of the elements of Article 338 of the Criminal Code was not fully fulfilled and the actions of the perpetrator fulfilled the elements of forced defense (noodweer) in accordance with Article 49 of the Criminal Code.